IoT Based Single Identification Database Model For Under Development Countries (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The Internet of Things is becoming one of the most primary topics of conversation in the World of information Technology. There is a huge revolution that comes with the internet of things. With its multi-disciplinary application growth, the Internet of Things has changed our lifestyle. In regular life, people need to provide their user information multiple times for creating any national or international document. In this paper, a simple central server-based database model is proposed to reduce people's struggle of providing the same information multiple times and also reduces the chance of redundancy of data. According to this proposed model, users need to provide their information only once, and can use the same information in multiple sectors. Users need to provide their identification number which is provided by the central server and fingerprint only to access previously stored personal data. Users can easily create or update any national or international document using those data. The goal of this proposed model is to make a central database model for people to reduce the hassle of creating or updating national or international documents.